Persepsi Wisatawan Pasar Terapung Dalam Pengembangan Ikon Pariwisata Kota Banjarmasin - Maryam Mustika; Maria Karulina; Siti Nurhidayah; Dewi Cahaya; Fraydi Oica Yehezkiel (FKIP, Universitas Palangka Raya, 2023)
The Floating Market is a traditional market of the tourism icon of Banjarmasin city South Kalimantan whose trading activities are carried out on river water using Jukung (small boats). The purpose of this study was to describe tourists' perceptions of the Lok Baintan Floating Market. The method in this research uses descriptive qualitative. Informants in this study were 10 tourists and 3 sellers at the Lok Baintan floating market through interviews, literature studies and documentation. Based on the results of the study found several things about the perception of tourists in the development of tourism in Banjarmasin, visitors stated the need to improve infrastructure facilities, public toilets, clean water, river cleanliness and security. There needs to be socialization for sellers in strategies to attract buyers so that there is no coercion in the buying and selling process and tourists do not feel uncomfortable. So that there are unscrupulous sellers who force visitors to buy their merchandise. It is hoped that this research can be a driver and solution in the development of the Floating Market as a traditional market, tourist attraction and source of the people's economy in South Kalimantan